Effect of pH and temperature on fibrous structure formation of plant proteins during high-moisture extrusion processing. (June 2022) - Nisov, Anni; Nikinmaa, Markus; Nordlund, Emilia; Sozer, Nesli
Graphical abstract: Highlights: All raw materials showed fibrous structure at elevated extrusion temperatures. Shift from pH 5 to pH 7 enhanced fibrous structure formation. Raw material characteristics followed isoelectric behaviour. Fibrous structure formation showed no correlation with protein's isoelectric point. Abstract: This study investigated the effect of pH on fibrous structure formation (protein alignment) during high-moisture extrusion processing of gluten, rice protein, as well as pea protein concentrate, and isolate. The pH of the raw material was shifted to 5 and 7 in water suspension with an acid or base and freeze-dried, after which, conductivity, solubility, water-holding capacity, particle size, and pH were measured. The pH-shifted raw materials were extruded at various temperatures (95–160 °C) and the extrudates were analysed for protein alignment (macro and microstructure), tensile strength, free thiol groups, and cooking properties. In general, all raw materials generated fibrous structure at lower temperatures (115–140 °C) at pH 7 than at pH 5 (135–160 °C). Higher pH and temperature values led to an increased tensile strength and pronounced protein alignment. No such unambiguous link could be observed between the raw material properties and enhanced structure formation. This study showed that the structure formation of the extrudate can be positively influenced by increasing the pH of the raw material, which facilitates the plant protein structuring into appealing meat analogue products.